The Influence of Parenting Dimensions on Children’s Adjustment: the role of Parent Gender. - Rodríguez-Menéndez, Carmen; García-Pérez, Omar; Martínez-García, Lindsay (Anales de Psicología / Annals of Psychology, 2026)
Self-determination Theory (SDT) recognizes that parents exert a determining influence on children’s well-being. In this context, the present study examined whether there were gender differences in parenting behaviors in accordance with Self-determination Theory (SDT) and analyzed how maternal and paternal parenting behaviors, and children’s gender, influence children’s outcomes (emotional instability, prosocial behaviors, and verbal and physical aggression). The participants comprised 2,404 parents from Spain and 1,325 children. Results found that mothers perceived themselves to be more autonomy supportive, more structured, and warmer and less controlling than fathers perceived themselves to be. Statistically significant differences were found according to the sex of the children. For higher emotional instability, mothers’ warmth and structure were protective factors, but fathers’ parenting practices had no influence. Maternal and paternal control were risk factors for developing higher emotional instability. The provision of an autonomous environment by fathers is important as a protective factor against the development high levels of physical and verbal aggression.